RETHINKING NATIONAL SECURITY POLICY: INDONESIA CASE - Riant Nugroho; Agustina Setiawan (Universitas Jenderal Ahmad Yani, 2025)
There is a 2nd generation of academical framework as a fit foundation for developing policy and practices of the national security policy in the developing countries, as a framework that enlarging the understanding from international and military studies into a wider of political studies. Academical discourse in Indonesia is now promoting the framework of total policy performance in which national security policy place at the center. The seminal method and measurement of national security performance that have been developed had scored Indonesia of 27.8875, which means a conducive performance.